ESPN's Broadcast Rights Protection in Intellectual Property Law Over World Cup Broadcast Piracy - Hasoloan Limbong, Albert (Journal of Law, Politic and Humanities, 2025)
Television broadcast piracy, especially in the broadcast of the World Cup by ESPN, has become a growing problem along with the advancement of digital technology. Broadcasting rights as part of Intellectual Property Rights (IPR) have high economic value and have received legal protection through various regulations, such as Law Number 28 of 2014 concerning Copyright and Law Number 1 of 2024 concerning Information and Electronic Transactions (UU ITE). However, the challenges in law enforcement are still quite substantial, especially related to cross-border piracy, difficulties in blocking illegal sites, and low public awareness of the impact of piracy. The Indonesian government, through the Ministry of Communication and Information (Kominfo), has made efforts to combat piracy by blocking illegal sites and implementing the "Trusted Flagger" mechanism. Meanwhile, broadcasting rights holders such as ESPN are also trying to protect their rights by collaborating with law enforcement and utilizing digital detection technology. This study highlights regulatory weaknesses that still need to be improved and recommends more effective policies, including strengthening international cooperation, implementing artificial intelligence-based technology to monitor illegal content, and increasing public education about broadcasting rights and the impact of piracy.